Metazoários parasitos de lambari astyanax altiparanae, Coletados do rio do Peixe, São Paulo, Sudeste do Brasil - Camargo, Aline de Almeida [UNESP] (2016)
In March 2010, 44 specimens of Astyanax altiparanae Garutti & Britski, 2000, commonly known as “lambari do rabo amarelo”, collected from the Peixe river in the state of São Paulo, Brazil were analyzed. Out of these 44 fishes, 38 had at least one species of metazoan parasite. Fifteen metazoan parasites species were collected and identified: Urocleidoides trinidadensis, Diaphorocleidus kabatai, Diaphorocleidus orthodusus, Diaphorocleidus sp., Urocleidoides sp., Trinibaculum altiparanae, Gyrodactylus sp., Jainus hexops, Contracaecum sp., Procamallanus (Spirocamallanus) inopinatus, Vaigamus sp., Amplexibranchius bryconis, Ergasilus sp., Zonocotyloides haroltravassossi and Henneguya sp. Six species of parasites presented a prevalence of over 10%. Weight and length of fishes didn’t influence the parasitism. All parasites presented an aggregated distribution. The parasite community of Astyanax altiparanae from the Peixe river was characterized as having high richness and low uniformity.